Interactive E-Modules with Discovery Learning: Increase Informatics Motivation for Vocational Students - Safrida, Neno Fani; Ramadhani, Farah; Agusty, Alifia Ilwi (Universitas Negeri Malang, 2023)
This research aims to develop and determine the feasibility of flipbook-based interactive e-modules in informatics subjects and determine student motivation after using the product. The development model applied is Hannafin and Peck with three stages, including (1) needs analysis, (2) design, and (3) development and implementation. Experts in learning media and material validated the product. Data was collected using a validation questionnaire sheet and distributing questionnaires with product feasibility instruments and learning motivation. The media expert validation assessment results get a 91 percent or very feasible percentage, while the material expert's percentage is 98.4 percent or very feasible. The small group testing was 93.44 percent or very feasible, and the extensive group testing was 88.58 percent or very feasible. Student learning motivation after using the product obtained a percentage of 87.21 percent, or very high. Thus, the interactive e-module product is considered capable of increasing student learning motivation and is very feasible to be used in the learning process at school.